(untitled) (Italian Journal of Public Health, 2005)
Italy is dealing with an early stage of Health Technology Assessment diffusion. In our opinion, there are at least three important dimensions related to Health Technology Assessment (strategy, inter-organisational relationships and governance) that are able to affect it, at each level, systemic and operating-unit related. Although Health Technology Assessment may have originated as a centralised function conducted by federal government agencies or other national/regional organisations, it is an increasingly decentralised activity. In Italy this decentralisation process is now reaching a peak because of the almost total assignment of health responsibilities to regional authorities. Moreover, Health Technology Assessment is interdisciplinary and it is interdependent with innovation processes. The context seems to be very complex: in our opinion a flexible approach is advisable. The following describes this new approach and the experiences in Lombardy where various solutions have been adopted to support and improve Health Technology Assessment processes.